2019
DOI: 10.1093/nar/gkz911
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of R882 change flanking sequence preferences of the DNA methyltransferase DNMT3A and cellular methylation patterns

Abstract: Somatic DNMT3A mutations at R882 are frequently observed in AML patients including the very abundant R882H, but also R882C, R882P and R882S. Using deep enzymology, we show here that DNMT3A-R882H has more than 70-fold altered flanking sequence preferences when compared with wildtype DNMT3A. The R882H flanking sequence preferences mainly differ on the 3′ side of the CpG site, where they resemble DNMT3B, while 5′ flanking sequence preferences resemble wildtype DNMT3A, indicating that R882H behaves like a DNMT3A/D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 57 publications
9
55
0
Order By: Relevance
“…Along the line, the enzymatic preference toward the flanking sequences of CpG target sites has previously been observed for both DNMT3A and DNMT3B [35][36][37][38] , yet the mechanism remains unclear. The enzymatic analysis in this study not only supports an earlier notion that the DNMT3A R882H mutation shifts the enzymatic preference of DNMT3A toward a purine (G or A) on the +1 flanking site 25 ( Supplementary Fig. 6d), but also indicates that the R882H mutation reduces the CpG/CpH specificity of DNMT3A, both of which presumably impact the DNA methylation landscape across the genome 25 .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Along the line, the enzymatic preference toward the flanking sequences of CpG target sites has previously been observed for both DNMT3A and DNMT3B [35][36][37][38] , yet the mechanism remains unclear. The enzymatic analysis in this study not only supports an earlier notion that the DNMT3A R882H mutation shifts the enzymatic preference of DNMT3A toward a purine (G or A) on the +1 flanking site 25 ( Supplementary Fig. 6d), but also indicates that the R882H mutation reduces the CpG/CpH specificity of DNMT3A, both of which presumably impact the DNA methylation landscape across the genome 25 .…”
Section: Discussionsupporting
confidence: 87%
“…The enzymatic analysis in this study not only supports an earlier notion that the DNMT3A R882H mutation shifts the enzymatic preference of DNMT3A toward a purine (G or A) on the +1 flanking site 25 ( Supplementary Fig. 6d), but also indicates that the R882H mutation reduces the CpG/CpH specificity of DNMT3A, both of which presumably impact the DNA methylation landscape across the genome 25 . Importantly, the crosstalk between the RD interface and the TRD loop provides a mechanism by which the R882H mutation affects the substrate specificity of DNMT3A.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, increasing evidence has indicated that the activity of DNMTs can be strongly influenced by sequences outside the core CpG site, called flanking sequence here. For instance, the DNMT3 enzymes have been reported for their pronounced flanking sequence preferences [19][20][21][22][23][24][25] . Recently, it has even been demonstrated that alteration of the flanking sequence preferences of DNMT3A provides a key mechanistic basis for cancer promoting effects of the somatic DNMT3A R882H mutation, which is frequently observed in acute myeloid leukemia (AML) 23,24 .…”
mentioning
confidence: 99%